2008
DOI: 10.15388/socmintvei.2008.1.6051
|View full text |Cite
|
Sign up to set email alerts
|

Atotolio šeima: nauja užduotis šeimos sociologijai

Abstract: Šeimos narių laikina emigracija iš Lietuvos nėra naujas reiškinys, tačiau jo mastai tampa iššūkiu šeimos institutui. Susiduriama su naujais reiškiniais: vienas arba abu tėvai išvyksta į užsienį, o vaikai gyvena Lietuvoje vieni, globojami giminių, valstybės. Kaip vertinti šiuos šeiminio gyvenimo pokyčius? Ar šie transnacionaliniai šeiminiai dariniai taps alternatyva branduolinei šeimai, kaip kadaise ja tapo sugyvenimas, švytuoklinės šeimos, sambūvis pavieniui? Akistata su nauju šeiminiu dariniu skatina klausti:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our analysis of transnational family representations in the public discourse showed that migrant family life has created new sources of social stigma. The examples of such stigma could be found in our study of how Lithuanian dailies and the Internet portal Delfi portray migrant families and left-behind children as well as in our overview of routine daily situations where these children would be stigmatized (Juozeliūnienė et al, 2008). We have further analyzed how the representations of migrant families within meaning-making institutions like the Lithuanian legislation on managing migration flows and TV documentary films (2006)(2007)(2008)(2009)(2010) are shaped by official family ideology and internal ideology espoused by the editorial boards of the TV channels.…”
Section: Researching Transnational Families In Their Own Rightmentioning
confidence: 92%
“…Our analysis of transnational family representations in the public discourse showed that migrant family life has created new sources of social stigma. The examples of such stigma could be found in our study of how Lithuanian dailies and the Internet portal Delfi portray migrant families and left-behind children as well as in our overview of routine daily situations where these children would be stigmatized (Juozeliūnienė et al, 2008). We have further analyzed how the representations of migrant families within meaning-making institutions like the Lithuanian legislation on managing migration flows and TV documentary films (2006)(2007)(2008)(2009)(2010) are shaped by official family ideology and internal ideology espoused by the editorial boards of the TV channels.…”
Section: Researching Transnational Families In Their Own Rightmentioning
confidence: 92%
“…In regard to Lithuania, by 2006, emigration was already established as an important theme in the media (Budginaitė, 2012), and the impact of emigration on family life had started to become a prominent worry, causing anxiety about ‘family destruction’ (Juozeliūnienė et al, 2008). The analysis of articles’ headings and content revealed that the representation of transnational families in the articles and Internet portals in Lithuania commonly focus on troubling parenting across borders, which is contrasted with the key moral imperative concerning the requirement to be responsible parents (Juozeliūnienė et al, 2008).…”
Section: Portraying Transnational Motheringmentioning
confidence: 99%
“…In regard to Lithuania, by 2006, emigration was already established as an important theme in the media (Budginaitė, 2012), and the impact of emigration on family life had started to become a prominent worry, causing anxiety about ‘family destruction’ (Juozeliūnienė et al, 2008). The analysis of articles’ headings and content revealed that the representation of transnational families in the articles and Internet portals in Lithuania commonly focus on troubling parenting across borders, which is contrasted with the key moral imperative concerning the requirement to be responsible parents (Juozeliūnienė et al, 2008). Moreover, such troubling constructions were largely associated with transnational mothering and, echoing the previous research studies (Duncan and Edwards, 1999; Ribbens McCarthy et al, 2000), reflected the gendered ways in which moral standing is particularly at stake in relation to the care of children.…”
Section: Portraying Transnational Motheringmentioning
confidence: 99%
“…People residing in Lithuania but willing to maintain relationship with emigrant family members plan the events of their lives respectively (Mikulionienė, 2013;2014). Other aspects of Lithuanian families related to migration have also been researched: Maslauskaitė (2009c) revealed the genesis and development prospects of the family living across borders; Juozeliūnienė et al (2008) analyzed the methodological specificities of research on such families, etc. However, there is still little data on the activities (practices) important for doing family in the context of mass migration, and how family practices are related to personal networks.…”
Section: Introductionmentioning
confidence: 99%